Daucus Carota oil extract, a chemotherapeutic agent, acts as an antidepressant that promotes resilience to chronic social defeat stress - Houbeika, Rouba (2021)
Cancer is second leading cause of death worldwide affecting more than 15 million individuals. Many risk factors play an important role in the development of cancer. These alterations give rise to cancerous cells with an ability to grow, divide and proliferate indefinitely. Multiple pathways are involved in cancer propagation. The survival and spreading of cancerous cells are regulated by the MAPK/ERK and PI3K/AKT pathways. Major depressive disorder is a mental illness diagnosed in many cancer patients. It is characterized by a decrease in hippocampal size and disruption of normal synaptic plasticity. A decrease in the hippocampal p-Akt protein levels is observed in depressed subjects. In addition, the MAPK/ERK pathway has been extensively studied and targeted for therapies. In addition, a decrease in the hippocampal brain derived neurotrophic factor (BDNF) protein level has been reported in postmortem human brains of depressed patients. Daucus carota L. ssp. Carota commonly known as the wild carrot is grown in Lebanon. It is used as folk medicine to treat many diseases such as diabetes mellitusand cancer. β-2-himachalen-6-ol (HC-6-ol), its major compound, causes a dose-dependent decrease in cell viability, induces cell cycle arrest, and promotes apoptosis in cancer cells. In this study, we used the chronic social defeat stress model to induce depressive-like behaviors in mice and studied the effect of the Daucus carota oil extract (DCOE) and HC-6-ol on social behavior following chronic stress. Our work revealed that DCOE promoted resilience to chronic stress independent from its major active component HC-6-ol. In contrast, when used as therapies to rescue depressive-like behaviors, both the DCOE and β-2-himachalen-6-ol were equally efficient. Our results suggest that different components of DCOE are responsible for its preventative effects as compared its therapeutic effects. Finally, our results could possibly implicate the hippocampal AKT pathway in the therapeutic effect of DCOE and HC-6-ol.